Correlation between Length-to-width Ratio of Gallbladder and Gamma-glutamyl Transferase Value in Biliary Atresia - Elmanar, Ryan; Violetta, Lenny; Setiawati, Rosy (Universitas Islam Bandung, 2024)
Biliary atresia represents one of the most prevalent etiologies for neonatal cholestasis. Unmanaged biliary atresia can be fatal. Ultrasonography is the primary diagnostic test because it's accurate, cost-effective, and available. Various ultrasound findings can assist in diagnosing biliary atresia; the length-to-width ratio of the gallbladder is a particularly advantageous method, offering a short examination time, objectivity, and ease of use, with an accuracy rate of 78.9%. In cases with unconventional ultrasound findings, gamma-glutamyl transferase is believed to be able to complete the diagnostic process with an accuracy rate of up to 80%. The optimal cut-off value differs between studies, making it challenging to use as a benchmark for biliary atresia detection. In this study, researchers aim to further investigate the relationship between length-to-width ratio and gamma-glutamyl transferase in cases of biliary atresia, compared to the liver biopsy results in these patients and the optimal cut-off. This study employed an observational analytic approach with a retrospective design. The sample population consisted of all patients with neonatal cholestasis who underwent laboratory and ultrasonographic examinations at Dr. Soetomo Academic General Hospital Surabaya between 2019 and 2023. The study population comprised 82 patients. A significant relationship (p-value<0.001) was observed between the length-to-width ratio of the gallbladder and biliary atresia, as well as between gamma-glutamyl transferase and biliary atresia (area under the curve: 0.7–0.8). However, the analysis between the length-to-width ratio of the gallbladder and the value of gamma-glutamyl transferase showed p-value=0.066, which means no significant relationship was observed between the length-to-width ratio and gamma-glutamyl transferase. DOI: https://doi.org/10.29313/gmhc.v12i3.14170